Yeast fermentation in a cocurrent downflow contacting reactor (CDCR) - Özer, A; Dursun, G; Özer, D; Elibol, M (John Wiley & Sons Ltd, 2000)
The growth kinetics and mass transfer characteristics of Saccharomyces cerevisiae in a cocurrent downflow contacting reactor (CDCR) were studied for various glucose concentrations at constant air and liquid flow rates. Increasing glucose concentration increased the biomass concentration thus resulting in an increase in the volumetric oxygen uptake rate. The volumetric mass transfer coefficient, k(L)a, however, decreased with increasing glucose concentration, It was observed that the growth of S cerevisiae in the CDCR would fit the classical Monod kinetics and the maximum specific growth rate was determined to be 0.545 h(-1) (C) 2000 Society of Chemical Industry.
Keywords: yeast; Monod kinetics; cocurrent downflow contacting reactor; fermentation